2019
DOI: 10.3390/separations6020026
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Techniques in the Research Area of Lithium Ion Batteries: Current State-of-the-Art

Abstract: Lithium ion batteries (LIBs) are widely used in numerous application areas, including portable consumer electronics, medicine, grid storage, electric vehicles and hybrid electric vehicles. One major challenge during operation and storage is the degradation of the cell constituents, which is called aging. This phenomenon drastically reduces both storage lifetime and cycle lifetime. Due to numerous aging effects, originating from both the individual LIB cell constituents as well as their interactions, a wide var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 249 publications
(407 reference statements)
1
47
0
Order By: Relevance
“…Besides electrochemical decomposition, thermal stress at elevated temperatures (60–80 °C) is another reason for a ring opening polymerization of ethylene carbonate (EC) and a comparable variety of species . Overall, the identified soluble compound classes in electrolytes covered (i) oligo carbonates, (ii) carbonate ether co‐oligomers, (iii) glycols, (iv) O(F)Ps, (v) phosphate‐carbonate‐intermixtures and (vi) oligo phosphates, resulting in various different species …”
Section: Introductionmentioning
confidence: 99%
“…Besides electrochemical decomposition, thermal stress at elevated temperatures (60–80 °C) is another reason for a ring opening polymerization of ethylene carbonate (EC) and a comparable variety of species . Overall, the identified soluble compound classes in electrolytes covered (i) oligo carbonates, (ii) carbonate ether co‐oligomers, (iii) glycols, (iv) O(F)Ps, (v) phosphate‐carbonate‐intermixtures and (vi) oligo phosphates, resulting in various different species …”
Section: Introductionmentioning
confidence: 99%
“…[28,29] Besides electrochemical decomposition, thermal stress at elevated temperatures (60-80 8 8C) is another reason for aring opening polymerization of ethylene carbonate (EC) and acomparable variety of species. [25,[30][31][32][33] Overall, the identified soluble compound classes in electrolytes covered (i)o ligo carbonates,(ii)carbonate ether co-oligomers,(iii)glycols,(iv) O(F)Ps,(v) phosphate-carbonate-intermixtures and (vi)oligo phosphates,r esulting in various different species. [25,28,29,34,35] Particularly,the decomposition route to oligo phosphates via "intermediary A" was difficult to define.Recently,W ang, Xu, Eichhorn and co-workers corrected the previous assumption of lithium ethyl di-carbonate (LEDC) as am ain SEI component to the analogous monocarbonate species.…”
Section: Introductionmentioning
confidence: 99%
“…There are many research papers on SEI formation, and several excellent reviews. [1,[10][11][12][13] Generally, the emphasis is on SEI layer composition and morphology, typically as a function of electrolyte type and electrode surface structure. There has been previous work that correlates the SEI formation conditions to the subsequent cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…The SEI layer is extremely complicated, and various spectroscopic studies have identified many components. [12][13][14] The SEI is usually considered to be a heterogeneous mosaic of different organic, organo-metallic and inorganic phases. Different products are formed as the anode voltage decreases.…”
Section: Introductionmentioning
confidence: 99%